ANALISIS PERENCANAAN DAN PENJADWALAN BAHAN BAKU PRODUKSI DENGAN METODE MATERIAL REQUIREMENT PLANNING (Studi Kasus: Usaha Tahu H.Basri) - Prasetyo, Healthy Aldriany; Sanjaya, Frana; Zulvatricia, Reakha (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
H. Basri Tofu Business is a business that produces raw tofu or white tofu products, the company still uses conventional calculations in purchasing raw materials. The company purchases raw materials continuously which aims to make raw materials always available so that it is hoped that production activities can run smoothly, but there is often a shortage of raw materials or stock unavailability when tofu production is carried out because there is no scheduling of raw material purchases at H. Basri Tofu Business. What can be done for efficient raw material inventory is to apply the Material Requirement Planning (MRP) method which can determine the supply of raw materials used in making tofu, namely soybeans, tofu flour, and vinegar. To obtain the company's main target, namely getting maximum profit, the company is required to be able to maintain a balanced inventory level to prevent raw material shortages. This study uses the Material Requirement Planning (MRP) method with the Lot for Lot technique using data on the use of raw materials for H. Basri's Tofu Business in the period December 2024 to March 2025 which in the calculation of the supply of raw materials in the tofu production process at H. Basri's Tofu Business is the Lot for Lot technique which is carried out on a weekly basis is the calculation with the smallest total cost of Rp 1,188,646.